A Multiscale Characterization of Two Tropical Embiopteran Species: Nano- and Microscale Features of Silk, Silk-Spinning Behavior, and Environmental Correlates of their Distributions. Issue 5 (22nd July 2020) - Shenoy, Samantha; Ing, Keilyn; Barber, Richard P; Rooks, Edward C; Edgerly, Janice S
Abstract: Embioptera display the unique ability to spin silk with their front feet to create protective domiciles. Their body form is remarkably uniform throughout the order, perhaps because they all live within the tight confines of silken tubes. This study contributes to an understanding of the ecology of Embioptera, an order that is rarely studied in the field. We conducted a census to quantify the habitats of two species with overlapping distributions on the tropical island of Trinidad in a search for characteristics that might explain their distinct ecologies. One species, Antipaluria urichi (Saussure) (Embioptera: Clothodidae), lives in larger colonies with more expansive silk in habitats throughout the island, especially in the rainforest of the Northern Range Mountains. The other, Pararhagadochir trinitatis (Saussure) (Embioptera: Scelembiidae), was found only in lowland locations. We quantified silk-spinning behavior and productivity of the two species and found that A. urichi spins thicker silk sheets per individual and emphasizes spin-steps that function to create a domicile that is more expansive than that produced by P. trinitatis. Their silks also interact differently when exposed to water: the smaller-diameter silk fibers of P. trinitatis form more continuous films on the surface of the domicile after being wetted and dried than that seen in A. urichi silk. This tendency gives P. trinitatis silk a shiny appearance in the field compared to the more cloth-like silk of A. urichi . How these silks function in the field and if the differences are partially responsible for the distinct distributions of the two species remain to be determined.